Pelatihan Diversifikasi Olahan Produk berbahan Beras Hitam untuk Meningkatkan Nilai Ekonomi di Desa Glesungrejo Kabupaten Wonogiri - M. Al Haris; Nurhidajah; Amin Samiasih; Fitri Anjani; Alya Febriyani; Ayesha Nayla Salsadella; Anne Mutiara Wardani; Aulia Dewi Gustiarni; Syafina Amira Firdaus; Ilham Khairul Anam; Marsela Ayu Irdiana; Miftakhurizki; Mualim Tahari (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Glesungrejo Village, located in Baturetno Subdistrict, Wonogiri Regency, possesses considerable agricultural potential, with the majority of its population engaged in farming. Nevertheless, this potential has not yet provided optimal contributions to the local economy due to limitations in managing agricultural products to enhance their added value. This condition underscores the need for integrative strategies that can link the utilization of natural resources with the strengthening of the local economy in a sustainable manner. Through a grant from the Ministry of Education, Culture, Research, and Technology under the Community Empowerment scheme, the Student Executive Board of the Faculty of Agricultural Science and Technology, Universitas Muhammadiyah Semarang (BEM FSTP UNIMUS), initiated a program to develop innovations in local agricultural products. The program involved the Women Farmers’ Group (Kelompok Wanita Tani/KWT) as the primary partner in improving product quality and added value, with a focus on the flagship commodity of black rice. The outcomes demonstrated a significant improvement in participants’ understanding of black rice processing, ranging from drying using a cabinet dryer, flour production, to the formulation of food products such as cookies, snack bars, muffins, and herbal beverages. In addition to technical skill enhancement, participants were also able to operate production equipment independently. The establishment of micro-enterprises and the emergence of local cadres as community facilitators serve as indicators of the program’s success in fostering socio-economic empowerment based on post-harvest innovation. Overall, this initiative contributes to strengthening community capacity and enhancing the competitiveness of agricultural products.